MODEL TRIADIK CITRA KOTA GORONTALO BERBASIS KESENIAN, ARSITEKTUR TRADISIONAL, DAN SIMBOL KEISLAMAN - Dara Fitriani; Zuhriati A Djailani; Asta Juliarman Hatta (Universitas Katolik Soegijapranata, 2026)
This study aims to explore public perceptions of the cultural elements that shape the image of Gorontalo City. Amid rapid urban development that may gradually erode local wisdom values, strengthening the city’s identity has become increasingly important. Although Gorontalo’s cultural identity and city image have been widely discussed, studies examining cultural elements as determinants of city image from the community’s perspective remain limited. This research employs a qualitative approach using grounded theory. Data were collected through in-depth interviews, field observations, and open-ended questionnaires involving 100 respondents from Gorontalo City. The data were analyzed through open coding, axial coding, and selective coding to identify key categories and the relationships among cultural elements.The findings reveal that the image of Gorontalo City is shaped by three main clusters: Artistic Motifs, Traditional Architecture, and Islamic Symbols. Karawo, Pateda, Wulunga, and Manggis motifs emerge as the most recognizable aesthetic markers, while Pahangga, Makuta, and Tuwango represent the city’s architectural identity. Islamic symbols, including calligraphy, domes, and jalamba, further reinforce Gorontalo’s religious character as the “Veranda of Medina.” The study develops a Triadic Model of Gorontalo City Image, which explains the integration of aesthetic, structural, and spiritual values in shaping the city image and provides a conceptual framework for culturally based urban design and development.